On Fuzzy Quasi Filter Topological R-Module Spaces - Basim Mohammed Melgat (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This article deals with a new concept in the subject of fuzzy topological R-Module spaces is said fuzzy quasi Filter via fuzzy open quasi Filter sets and fuzzy closed quasi Filter sets and also present definitions for the Mixed fuzzy quasi Filter with this scope work and we briefly shows some features of fuzzy functions.